Establishing an antimicrobial stewardship centre of excellence: A global health partnership between KNUST University hospital & Ulster University - Aaron J Courtenay; Ahmed Abuelhana; Jaquie Hanley; Kwame Ayisi Boateng; Obed Amponsah (Journal of Global Antimicrobial Resistance)
AIM: To create a sustainable global-health antimicrobial stewardship (AMS) focused partnership between Ulster University and Kwame Nkrumah University of Science and Technology (KNUST) University-hospital, enhancing clinical practices and patient outcomes. BACKGROUND: Since 2021, Ulster University and KNUST have collaborated to enhance AMS in Ghana and Northern Ireland aiming to build capacity, improve clinical practices, and foster interdisciplinary cooperation through the Commonwealth Partnerships for Antimicrobial Stewardship (CwPAMS) project, supported by the Tropical Health and Education Trust (THET). METHODS: 1. Point-Prevalence-Surveys were conducted at KNUST University-Hospital to assess antimicrobial usage and resistance patterns, providing data-driven insights for AMS strategies.2. Educational Interventions were delivered targeting multidisciplinary teams (medicine, pharmacy, nursing, laboratory) in Ghana.3. Knowledge Exchange was facilitated through exchange visits and virtual meetings, ensuring continuous collaborative development of AMS protocols. RESULTS: • AMS Committee has been established at KNUST and now recognised as a Centre-of-Excellence in Ghana.• The point-prevalence-surveys revealed critical insights into local antimicrobial usage. Indications for antibiotic recommendations were community-acquired infections (36.5%), surgical prophylaxis (26.1%), and hospital-acquired infections (15.7%).• Educational programs improved clinician knowledge and antimicrobial prescribing behaviours.• Collaborations have been strengthened through fostered strong professional relationships, promoting ongoing AMS innovation. CONCLUSIONS: This partnership demonstrates the power of international collaboration in combating antimicrobial resistance. The successful establishment of a robust AMS framework at KNUST offers a model for other low-resource settings. Sustained collaboration and support will be crucial for expanding these achievements, contributing to global antimicrobial resistance efforts, and aligning with UK Action-Plan 2024, THET, and CWPAMs AMS objectives.